Effect of Various Bulk Sweeteners on the Survivability of Lactobacillus casei 431 in Milk Chocolate: Rheological and Sensory Properties Analysis - Rad, Aziz H.; Pirouzian, Haniyeh R.; Toker, Omer S.; Konar, Nevzat (BENTHAM SCIENCE PUBL LTD, 2020)
Background: Probiotics are the most widely consumed functional food. Consumers demand the production of foods also in low-calorie forms. Objective: In this study, Lactobocillus casei 431 and various sweeteners were used in milk chocolate as prohiotic and bulking agents, respectively. Methods: Samples were prepared by using sucrose or optimum polyols combination. Chocolate samples were stored at two temperatures (4 degrees C and 20 degrees C) for 180 days and the viability of prohiotic cells was controlled with the purpose of specifying the presented storage temperature. Results: The highest prohiotic viability was determined in the samples produced with sucrose and stored at 4 degrees C. The cell counts were retained at the functional amount after maintenance for 6 months. Probiotic sucrose-free chocolate was more viscous than control chocolate, although displayed satisfactory sensory attributes. Conclusion: As a result, the sugared and sugar-free prohiotic milk chocolates could be stored at room temperature. Due to the acceptable number of probiotic cells. the sucrose-free chocolates containing probiotics were considered as functional foods.
Keywords: Sucrose-free; chocolate; probiotic; rheological; sensory attributes; Biochemistry & Molecular Biology; Pharmacology & Pharmacy